Positive Anti-Histone Antibodies in Patients with Polymyositis - Falah, Khoirul; Mulya, Deshinta Putri (Acta Interna The Journal of Internal Medicine, 2024)
Background. Polymyositis is an idiopathic inflammatory myopathy characterized by proximal symmetric muscle weakness, increased skeletal muscle enzyme levels, electromyographic abnormalities, and nonspecific muscle biopsy findings. Autoimmune mechanisms are thought to be the pathogenesis of the disease. Some autoantibodies have specificity and a high relationship with myositis.Case. A 23-year-old male presented with progressive quadriparesis, with predominant lower limb weakness, and severe myalgia of one-month duration, significantly impairing ambulation. He has a history of occupational exposure to propylene gas and atmer liquid while working in a plastic factory. Muscle strength in upper extremities were 4 and lower extremities were 3. Laboratory examination showed CK level 11856 U/L, SGOT 773 U/L, SGPT 486 U/L, LDH 1601 U/L, ANA IF 1:1000 with speckled pattern, normal electroneuromyography, anti-Histone antibodies (++). The patient refused a muscle biopsy. The patient met 2 of the 4 criteria so he was diagnosed with possible polymyositis and was treated with methylprednisolone injection 125 mg/ 6 hours for 3 days then tappering down , mycophenolate acid 2x180 mg , mecobalamin 2x500 mcg, and vitamin D 1x400 mg. After 1 month of therapy, muscle weakness improved and he was able to walk again.Discussion. Specific antibodies for myositis include antisynthetase, anti-Jo-1, anti-PL-7, anti-EJ, anti-PL-12, and anti-Mi-2, antibodies associated with myositis include anti-PM-Sci, anti-Ku , anti-KJ, anti-Ro/SSA.Anti-histone antibodies are commonly present in drug-induced lupus, but some studies have shown an association with other autoimmune and rheumatic diseases. Specificity pattern of serum anti-histone antibodies (AHA) on part of polymyositis patient similar with serum pattern of systemic sclerosis. Another study showed positive results in 17% of 46 polymyositis and dermatomyositis patients.Summary. A young man with clinical and laboratory criteria fulfilling the diagnosis of possible polymyositis, positive anti-histone antibodies were obtained, which is an antibody that is rarely found in cases of polymyositis.